2022
DOI: 10.3389/fpsyg.2022.923882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of homework creativity on academic achievement and creativity disposition: Evidence from comparisons with homework time and completion based on two independent Chinese samples

Abstract: During the past several decades, the previous studies have been focusing on the related theoretical issues and measuring tool of homework behaviors (mainly including homework time, completion, and homework creativity). However, the effects of these homework behaviors on general creativity remain unknown. Employing a number of questionnaires, this study investigated two samples from middle schools of Mainland China. The results showed that (1) the eight-item version of Homework Creativity Behaviors Scale had ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…According to Haq et al (2020), homework has a significant impact on student's achievement and varies depending on the age of the students. Moreover, Fan et al (2022) demonstrated that the eight-item version of the homework creativity behaviors scale had acceptable validity and reliability; homework creativity explained less variation in academic achievement than homework completion and homework time and homework creativity explained more variation in general creativity than homework completion and homework time. Contrary to popular belief, completing homework and having creative homework has a positive impact on students' overall creativity.…”
Section: Theme 2: Positive and Effects Of Homework Assignments On Ach...mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Haq et al (2020), homework has a significant impact on student's achievement and varies depending on the age of the students. Moreover, Fan et al (2022) demonstrated that the eight-item version of the homework creativity behaviors scale had acceptable validity and reliability; homework creativity explained less variation in academic achievement than homework completion and homework time and homework creativity explained more variation in general creativity than homework completion and homework time. Contrary to popular belief, completing homework and having creative homework has a positive impact on students' overall creativity.…”
Section: Theme 2: Positive and Effects Of Homework Assignments On Ach...mentioning
confidence: 99%
“…Duru and Cogman (2017) The aim of this study is to look into how primary and secondary school students and their parents feel about homework as well as the issues that arise when completing it from their perspective as parents. Fan et al (2022) The purpose of this study is to get a deeper understanding of homework creativity. Fatma (2014) The purpose of current study was to learn what middle school students' (n=705) opinions were regarding homework.…”
Section: Theme 1: Students' Teachers' and Parents' Views About Homewo...mentioning
confidence: 99%
See 1 more Smart Citation